Non-Speech Audio To Sustain Attention In A Multimedia E-Learning Environment - Yuen, May Chan (2007)
This experiment research examined the effects of sound, namely on non-speech sound in sustaining attention in a multimedia learning environment. As attention is prerequisite to learning, multimedia elements in an e-learning environment must first capture the learners' attention before any learning can take place.